-2=q+4

Simple and best practice solution for -2=q+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2=q+4 equation:


Simplifying
-2 = q + 4

Reorder the terms:
-2 = 4 + q

Solving
-2 = 4 + q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-1q' to each side of the equation.
-2 + -1q = 4 + q + -1q

Combine like terms: q + -1q = 0
-2 + -1q = 4 + 0
-2 + -1q = 4

Add '2' to each side of the equation.
-2 + 2 + -1q = 4 + 2

Combine like terms: -2 + 2 = 0
0 + -1q = 4 + 2
-1q = 4 + 2

Combine like terms: 4 + 2 = 6
-1q = 6

Divide each side by '-1'.
q = -6

Simplifying
q = -6

See similar equations:

| 4x^2-8=17 | | s-1=-3 | | 2=k+4 | | -63=7b | | 2-6n+2n=8-74 | | h+4=2 | | -16+2k=k-7k | | e+7=7 | | -13=n-4 | | j-1=-2 | | -5=g-5 | | -3x-7=2x+3 | | 5n-6n= | | -10p^2/3125-5p^2 | | -73+11y+9=4(4y-4)-8 | | -48=6(y+1) | | -7x+22=22 | | X^2-4x-44=-4 | | p-5(1-p)=-10p+(1-p) | | (x+2y)*dx+y*dy=0 | | N^2-12n-56=-8 | | 5x-3=3*(x+7)+3x | | q+10(1-q)=-5q+(1-q) | | 5(c-4)+3=2+c-19 | | q+(1-q)=-5q+(1-q) | | .6x-.2(10-3x)=-.4x-7 | | 9(w-5)=27 | | 18=-8x+66 | | 1+p=2p-1 | | 64v^3-t^3= | | 64ft^3-t^3= | | 4x^3+6x^2+1=0 |

Equations solver categories